2022
DOI: 10.1016/j.jht.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on hand therapy practice

Abstract: Highlights 86% of therapists reported feeling more stress than they did prior to the COVID-19 Older therapists and those that practiced longer felt more comfortable with in-person treatment. 98% of therapists reported a decrease in caseload. Post-operative cases and patients ages 19-49 were more likely to receive in-person treatment. 46% reported providing telehealth services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…28 Currently, the evidence related to efficacy of telehealth in hand rehabilitation as it relates to certain conditions or treatment approaches is lacking. In both the April 2020 survey 11 and in this survey, post-operative patients were significantly seen more in person than via telehealth. This signals that both the hand therapists and patients felt in person treatment was important after surgery despite the risk of COVID-19.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…28 Currently, the evidence related to efficacy of telehealth in hand rehabilitation as it relates to certain conditions or treatment approaches is lacking. In both the April 2020 survey 11 and in this survey, post-operative patients were significantly seen more in person than via telehealth. This signals that both the hand therapists and patients felt in person treatment was important after surgery despite the risk of COVID-19.…”
Section: Discussionmentioning
confidence: 82%
“…8 While front line workers and emergency personnel have been most notably impacted, the profound effects COVID-19 has had on the healthcare community reaches far beyond these limits to other allied health professions 9,10 , including the profession of hand therapy. 11,12 It was for this reason our first survey, "The impact of COVID-19 on hand therapy practice" 11 was developed and administered in April, 2020. In this initial survey, participants reported the abandonment of paraffin units and other modalities and the embracing of PPE; digital thermometers became commonplace, and human touch was eclipsed by telehealth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature published since the start of the pandemic, specific to hand therapy telehealth services, has primarily focused on the therapist experience of providing telehealth. 4 , 5 , 6 , 7 Szekeres and Valdes’ 7 survey of 819 therapists early in the COVID-19 pandemic (May 2020), that recruited from hand therapy associations in the United States, Canada, Australia and Europe, showed that very few therapists (n=38, 5%) had telehealth experience prior to the pandemic. The majority of therapists (n=557, 68%) reported they would be extremely or somewhat likely to continue with telehealth sessions once the pandemic settles.…”
Section: Introductionmentioning
confidence: 99%
“…A further survey of members of the American Society of Hand Therapists, conducted between April and May 2020, reported similarly low levels of pre-pandemic telehealth experience (4%). 4 Survey respondents were asked to reflect on the impact of COVID-19 on hand therapy practice, with some therapists expressing concern that telehealth would replace traditional therapy, while others welcomed the prospect of continued use of telehealth into the future. 4 The authors conducted a follow up survey between December 2020 and January 2021.…”
Section: Introductionmentioning
confidence: 99%